Research note: social catalysts in health promotion implementation - Rütten, Alfred; Abu-Omar, Karim; Levin, Lowell; Morgan, Antony; Groce, Nora; Stuart, Joanna (Journal of Epidemiology and Community Health, 2008)
Recent work carried out by WHO has recognised that an assets based approach to health promotion is crucial to support the promotion of population health and to reduce health inequalities. The assets approach was applied in a project aimed at promoting physical activity among women in difficult life situations. Within the participatory and collaborative work of the project, a specific set of assets for health that might initiate social participation and collaboration in health promotion action emerged. These assets are referred to as social catalysts for health promotion implementation. The article describes empowered individuals, informal social networks, mediating social institutions and organisational structures as potential social catalysts for health promotion implementation, and outlines some directions for further research on this topic.
UnivIS-Import:2015-03-09:Pub.2008.phil.dps.iss.lsw.resear